COMPARISON OF MONOCRYSTALLINE TYPES OF SOLAR CELL MODULES TO POLYCRYSTALLINE TYPES IN REVIEW OF THE POWER GENERATED BY APPLYING REAL-TIME MEASUREMENTS - Hamdani, Hamdani; Tharo, Zuraidah; Anisah, Siti (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The solar cell module is the main device in the solar power generation system. There are two types of solar cell modules that are commonly used, namely monocrystalline and polycrystalline types. The selection of the better type of solar cell module for a particular area, condition, and time can increase the effectiveness of solar power plants. This study aims to compare the performance of monocrystalline solar cell modules against polycrystalline solar cell modules in terms of the power generated when each solar cell module obtains the same intensity of sunlight. Measurements were carried out in two different weather conditions, namely when the sun was shining brightly and when the weather was cloudy or foggy. The measurement method was carried out by applying an automatic electronic data logger system. Data is retrieved in real-time and stored in the memory card. In addition to measuring the voltage, light intensity and surface temperature measurements were also carried out for each type of solar cell module. The results showed that the monocrystalline solar cell module produces a higher power than the polycrystalline type.